Community Service Teaching To Lecturers And Trainers At Pusdiklat Muhammadiyah University Of Malang - Tanti Widia Nurdiani; R. M Mahrus Alie (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Community service teaches to lecturers and trainers at the Training and Education Center of Muhammadiyah University of Malang (Pusdiklat UMM) plays a crucial role in enhancing the qualifications of lecturers and administrative staff to meet the established standards of human resources both nationally and internationally, in line with the dynamics of global human resource competencies. In this context, Smart Indonesia Academy, a management company, provides competency assessor training at Pusdiklat UMM as a community empowerment effort. This research adopts an analytical descriptive method to collect, analyze, and interpret data. The research findings indicate the smooth implementation of community service activities by Smart Indonesia Academy at the Pusdiklat UMM office. In conclusion, this study highlights the complexity and challenges of implementing competency-based training and education approaches in the workplace and higher education, emphasizing the importance of in-depth understanding and problem-solving efforts to enhance implementation effectiveness.